Development and Cytomolecular Identification of Monosomic Alien Addition and Substitution Lines of Triticale (×Triticosecale Wittmack) With 2Sk Chromosome Conferring Leaf Rust Resistance Derived From Aegilops kotschyi Boiss - Kwiatek, Michał T.; Ulaszewski, Waldemar; Belter, Jolanta; Phillips, Dylan; Skowrońska, Roksana; Noweiska, Aleksandra; Wiśniewska, Halina (Frontiers in Plant Science, 2020)
Alien chromosome introgression has become a valuable tool to broaden the genetic variability of crop plants via chromosome engineering. This study details the procedure to obtain monosomic addition and monosomic substitution lines of the triticale carrying 2Sk chromosome from Aegilops kotchyi Boiss., which harbors Lr54+Yr37 leaf and stripe rust resistant gene loci, respectively. Initially, Ae. kotschyi × Secale cereale artificial amphiploids (2n=6x=42 chromosomes, UUSSRR) were crossed with triticale cv. ‘Sekundo’ (2n=6x=42, AABBRR) in order to obtain fertile offspring. Cyto-molecular analyses of five subsequent backcrossing generations revealed that 2Sk chromosome was preferentially transmitted. This allowed for the selection of monosomic 2Sk addition (MA2Sk) lines of triticale. Finally, the 2Sk(2R) substitution plants were obtained by crossing MA2Sk with the nullisomic (N2R) plants of triticale. The presence of 2Sk chromosome in subsequent generations of plants was evaluated using SSR markers linked to Lr54+Yr37 loci. Disease evaluation of the monosomic 2Sk(2R) substitution plants for the reaction to leaf and stripe rust infection were carried out under controlled conditions in a growth chamber. The results showed significant improvement of leaf rust resistance severity of monosomic substitution plants compared to control (‘Sekundo’). In contrast, the introgression of the Lr54+Yr37 loci did not lead to improvement of stripe rust resistance. In summary, the creation of monosomic addition and monosomic substitution lines of triticale is the starting point for the precise and guided transfer of Lr54+Yr37 loci. The results showed that the developed materials could be exploited for the development of triticale varieties with resistance to leaf rust.